Comparison between Calibration and Addition Method of Lead and Chromium Total Testing in Textile Industrial Wastewater using AAS - Dyah Marganingrum; Ayunda Sean; Etih Hartati (Universitas Diponegoro, 2022)
Most of the wastewater from the textile industry in Indonesia has a negative impact on the environment and society. The wastewater contains heavy metals such as lead (Pb) and total chromium (Cr-Tot) from the coloring process. Pb and Cr-Tot parameters testing usually use Atomic Absorption Spectrophotometer (AAS). The purpose of this study was to compare between the calibration and the addition method to test the metal parameters of Pb and Cr-Tot contained in wastewater of textile industry of PT. X. Calibration method is often use for heavy metal concentration test than addition method. However calibration method is not frequently used for low concentration while addition method can be used for that. The difference between two methods is in the procedure. The concentrations of Pb and Cr-Tot using calibration method were 0.058 mg/L and 0.018 mg/L, respectively. Meanwhile, the concentrations of Pb and Cr-Tot using the addition method were 1.1419 mg/L and 1.1036 mg/L, respectively. Based on this research, the addition method gives a relatively better value and fulfills the interval requirements in the AAS readings for low Pb metal concentrations.